Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41388-021-01724-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo CRISPR inactivation of Fos promotes prostate cancer progression by altering the associated AP-1 subunit Jun

Abstract: Prostate cancer is a major global health concern with limited treatment options for advanced disease. Its heterogeneity challenges the identification of crucial driver genes implicated in disease progression. Activating protein-1 (AP-1) transcription factor is associated with cancer since the first identification of its subunits, the proto-oncogenes JUN and FOS. Whereas both JUN and FOS, have been implicated in prostate cancer, this study provides the first functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…This method ensures simultaneous, multiplexed gene editing in adult mice and therefore bypassing timely breeding schemes. Another advantage of this method is the targeting of only few cells in the prostate epithelium, which allows tumor cells to clonally expand, similar to human cancer initiation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This method ensures simultaneous, multiplexed gene editing in adult mice and therefore bypassing timely breeding schemes. Another advantage of this method is the targeting of only few cells in the prostate epithelium, which allows tumor cells to clonally expand, similar to human cancer initiation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, we analyzed FOS expression at different stages of PCa from publicly available datasets. Our analyses revealed that FOS expression is decreased in advanced disease and further downregulated in metastatic PCa [ 11 ]. This indicated that FOS acts as a tumor suppressor gene in PCa progression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CRISPR/Cas9 system induces mutations at the sgRNA target site by deletions or insertions (Indel) of base pairs, which often disrupt the reading frame [ 16 ]. The CRISPR/Cas9 system has been applied to in vivo studies and is widely used in mouse studies [ 16 , 17 , 18 ]. The method has multiple advantages, especially by simultaneous multiplex gene alteration in somatic cells.…”
Section: Introductionmentioning
confidence: 99%